Improving the thermoelectric properties of zinc tin oxide thin films by varying post growth annealing duration. Issue 22 (15th November 2021) - Rehman, Ubaid ur; Kanwal, M.; Mahmood, K.; Ashfaq, A.; Ali, A.; Tahir, S.; Sahar, Kashaf ul; Naeem, M.; Hussain, S.
Abstract: In this research work, we have successfully improved the thermoelectric properties of Zinc tin oxide thin films by controlling the post annealing duration. Initially, zinc tin oxide thin films were grown by direct evaporation of zinc and tin metal powder using the thermal evaporation method. After deposition, post growth annealing of the grown thin films was performed at 500 °C for different annealing durations (0.5, 1, 1.5 & 2 h). XRD data show the structural transformation from amorphous to mixed phases of Zn2 SnO4, ZnSnO3, ZnO, and SnO2 with the increase in post-growth annealing duration. While the sample annealed for 2 h represent only two phases of ZnO and ZnSnO3 . UV–vis data shows the decrease in band gap value from 3.8 to 3.61 eV with the increase in annealing duration. Seebeck data suggested the improvement in the Seebeck coefficient value from 24 to 104 μV/ ° C with the increase in annealing time duration while the electrical conductivity value was also improved from 34 to 63 S/cm. This increase in Seebeck coefficient and electrical conductivity was associated with the phase transformation into ZnSnO3 by suppression of un-wanted secondary phases leads to a high power factor up to 3.1 × 10 −4 Wm −1 K −2 . In addition, we have also performed Raman and SEM as supplementary measurements to support our purposed argument. Highlights: Growth of zinc tin oxide thin films on glass substrate by thermal evaporation method. Post annealing of the thin films were performed at 500 °C for different annealing time duration. XRD data suggested the suppression of un-wanted secondary phases for annealing duration of 2 h. Seebeck coefficient and electrical conductivity is significantly improved with the increase in annealing time duration.